Significance of Simultaneous Use of Different Methods for Interpretation of Internal Quality Control Data: An Experience of a Tertiary Care Hospital - Yadav, Shakti Kumar; Kalra, Rupinder; Jahan, Aarzoo; Pruthi, Sonam Kumar; Sarin, Namrata; Singh, Sompal; Singh, Harsh Vardhan (Annals of Pathology and Laboratory Medicine, 2020)
Background: Quality control is an essential part of quality management in medical laboratory. Various methods are available for the analysis of laboratory quality control data, common ones are Levey Jennings chart and Westgard rules. Westgard multi-rules are a set of rules based on combination of criteria to decide whether an analytical run is acceptable or unacceptable. CUSUM uses the cumulative sum of deviations from a target, however, it is rarely used in current medical laboratory practice. We share our experience of using Westgard rules and CUSUM in the analysis of laboratory quality control data. Material and methods: Internal quality control values of 2-year period was included in the present study. Data for platelet count values of normal level control material run on a fully automated haematology analyser (Sysmex XT-2000i) were analysed. A total of 1825 data points were obtained. The data was interpreted by Westgard rules as well as cumulative sum method. The out of control events was analysed. Results: There was 9 incidence of control value outside 3SD (Westgard Rule 13s) which was picked on Levey Jennings chart but missed by CUSUM method. There were 22 instances of shift in mean (bias) which were only picked by CUSUM method. Conclusion: CUSUM was more sensitive for detection of bias whereas random error was picked-up early by Westgard rules. In conclusion we recommend the use of more than one method for analysis of quality control data.